From Hope To Burden: A Mixed Methods Analysis Of The Psychosocial Impact And Financial Stress Of Online Loan Borrowers In Jakarta - Budi Safari; Dewi Endah Fajariana; Andarias Sambo; Haspul Naser; Nurwulan Kusuma Devi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The use of online lending (pinjol) often leads to urgent psychosocial pressure and financial stress for borrowers. As a result, m any borrowers become trapped in a cycle of debt that leads to immediate financial strain, decreased quality of life, and mental and social health problems. Therefore, this study aims to analyze the psychosocial impacts and measure the level of financial stress experienced by pinjol borrowers in Jakarta. Mixed methods approach with an exploratory sequential design with a total of 166 respondens. The study offers an integrated analysis of psychological, social, and economic aspects within a single framework, focusing on the urban context that has not been widely explored. Findings indicate that most respondents experienced psychological pressure, with 53% reporting anxiety and 43% experiencing social pressure due to societal stigma. More than 48% of respondents reported high levels of financial stress, with 51% citing non-transparent interest rates and aggressive debt collection practices as contributing factors. The psychosocial impacts of online lending as well as high interest rates and repetitive debt cycles often lead to emotional strain, helplessness, and ongoing stress. Borrowers who lack financial literacy are more vulnerable to risky lending practices.